Psychiatric manifestations of rheumatic diseases - Wróblewski, Hubert; Chojęta, Dariusz; Zimna, Aleksandra; Zygmunt, Ewelina; Kozłowska, Anna; Mierzwa, Monika; Wróblewska, Kinga (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work: Rheumatic diseases are chronic diseases that cause symptoms in many systems of the human body. Their most common symptoms include pain and symptoms of arthritis, their deformities, fatigue, and malaise. The aim of the article is to present the symptoms and mental disorders occurring in the course of selected rheumatic diseases. State of knowledge: The psychological symptoms are characteristic of systemic lupus erythematosus. Specified is a form of lupus called NSPLE (neuropsychiatric systemic lupus erythematosus), which includes neuropsychiatric symptoms in the course of systemic lupus erythematosus. Psychiatric symptoms are also present in the course of other rheumatic diseases. Neuropsychiatric symptoms may affect up to 80% of patients with primary Sjogren's syndrome, with 50% to 80% ahead of diagnosis. It has been proven that systemic slcerosis causes microvascular damage, which may cause neuropsychiatric symptoms in the form of mood disorders, anxiety and cognitive disorders. In one study, 59% of patients with fibromyalgia experienced mania, which was more than twice as high as in the control group. Summary: In the course of all rheumatic diseases presented by us, there are symptoms and mental disorders. They are often mood, cognitive and sleep disturbances. It should be emphasized that the etiology of psychiatric symptoms is multifactorial.